Statins as the Controlling Agents for Non-Hodgkin's Lymphomas via Increasing the Casein Kinase 2 Interacting Protein-1: A Hypothesis - Kazemi, Kimia; Mozafari, Negin; Ashrafi, Hajar; Rafiei, Pedram; Azadi, Amir (Current Drug Discovery Technologies, 2020)
Background: Non-Hodgkin's lymphomas (NHL), derived from B- or T-cell, consist of a heterogeneous group of malignant lymphoproliferative disorders. Knockdown of Casein kinase 2 interacting protein-1 (CKIP-1) in NHL promoted cell proliferation and inhibited apoptosis via enhancing phosphorylated Protein Kinase B (PKB or AKT) expression. Statins are the class of drugs that inhibit the ratelimiting step of the mevalonate pathway, which is essential for the biosynthesis of various compounds, including cholesterol. Also, statins have anticancer properties being mediated by different mechanisms. Methods: A search on databases like Scopus and PubMed with keywords such as statin and non- Hodgkin's lymphomas was performed and Kyoto Encyclopedia of Genes and Genomes (KEGG) website was used to evaluate and reconfirm the involved cellular signaling pathway. Results: CKIP-1 is involved in the regulation of cell proliferation and apoptosis while plays an important role in many cancers. We can hypothesize that statins may increase the expression levels of CKIP-1 which could contribute to the reductions in phospho-AKT level. Hence, they may ameliorate the NHL patients via suppressing AKT phosphorylation and increasing CKIP- expression. Conclusion: Present review confirms the positive effect of statins on NHL by increasing CKIP-1 and reducing cell proliferation, subsequently.
Keywords: AKT